Extraction of Sungkai (Peronema cannescens Jack) leaves, Antioxidant Activity Test and Its Nanoemulsion Formulation - Nurfauziyah; Yulizar Yoki; Meliana Yenny (E3S Web of Conferences, 2024)
Sungkai (Peronema canescens J.) is an Indonesian native plant widely distributed on the islands of Kalimantan and Sumatra. Potential of these plants is related to the presence of secondary metabolites, which can be obtained through extraction. In its application, plant extract requires a delivery system that can penetrate well into the skin and maximise the efficacy of the active ingredients, such as nanoemulsion, which has high kinetic stability due to the smaller droplet size. The research was conducted to compare the yields from the two extraction methods, the presence of active compounds in the plants related to their properties as antioxidants and then formulated into nanoemulsion. The results showed that Sungkai leaves extract contains active metabolites such as alkaloids, flavonoids, tannins and saponins. The extraction of sungkai leaves yields 15.91% and 14.71% for CE and UAE methods. The total phenolic and flavonoid values were 27.74 and 41.88 mg GAE/g extract; 17.60 and 36.02 mg QE/g extract; and IC50 values of 50.78 and 53.50, included in the strong antioxidant category. Stable nanoemulsion formulation was obtained by adding 1 gram of olive oil with a homogenisation speed of 15000 rpm, with particle size of 83.4 nm and a polydispersity index of 0.455.